Dampening effects of long-term experimental drought on growth and mortality rates of a Holm oak forest (GLOBAL CHANGE BIOLOGY, 2013)
Forests respond to increasing intensities and frequencies of drought by reducing growth and with higher tree mortality rates. Little is known, however, about the long-term consequences of generally drier conditions and more frequent extreme droughts. A Holm oak forest was exposed to experimental rainfall manipulation for 13years to study the effect of increasing drought on growth and mortality of the dominant species Quercus ilex, Phillyrea latifolia, and Arbutus unedo. The drought treatment reduced stem growth of A. unedo (-66.5%) and Q. ilex (-17.5%), whereas P. latifolia remained unaffected. Higher stem mortality rates were noticeable in Q. ilex (+42.3%), but not in the other two species. Stem growth was a function of the drought index of early spring in the three species. Stem mortality rates depended on the drought index of winter and spring for Q. ilex and in spring and summer for P. latifolia, but showed no relation to climate in A. unedo. Following a long and intense drought (2005-2006), stem growth of Q. ilex and P. latifolia increased, whereas it decreased in A. unedo. Q. ilex also enhanced its survival after this period. Furthermore, the effect of drought treatment on stem growth in Q. ilex and A. unedo was attenuated as the study progressed. These results highlight the different vulnerabilities of Mediterranean species to more frequent and intense droughts, which may lead to partial species substitution and changes in forest structure and thus in carbon uptake. The response to drought, however, changed over time. Decreased intra- and interspecific competition after extreme events with high mortality, together with probable morphological and physiological acclimation to drought during the study period, may, at least in the short term, buffer forests against drier conditions. The long-term effects of drought consequently deserve more attention, because the ecosystemic responses are unlikely to be stable over time.Nontechnical summaryIn this study, we evaluate the effect of long-term (13years) experimental drought on growth and mortality rates of three forest Mediterranean species, and their response to the different intensities and durations of natural drought. We provide evidence for species-specific responses to drought, what may eventually lead to a partial community shift favoring the more drought-resistant species. However, we also report a dampening of the treatment effect on the two drought-sensitive species, which may indicate a potential adaptation to drier conditions at the ecosystem or population level. These results are thus relevant to account for the stabilizing processes that would alter the initial response of ecosystem to drought through changes in plant physiology, morphology, and demography compensation.

Instantaneous and historical temperature effects on α -pinene emissions in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Llusia, Joan; Niinemets, Ülo; Noe, Steffen M.; Penuelas, Josep (Journal of Environmental Biology, 2011)
We compared the role of instantaneous temperature and temperature history in the determination of α-pinene emissions in Mediterranean conifer Pinus halepensis that stores monoterpenes in resin ducts, and in Mediterranean broad-leaved evergreen Quercus ilex that lacks such specialized storage structures. In both species, α-pinene emission rates (E) exhibited a significant exponential correlation with leaf temperature and the rates of photosynthetic electron transport (JCO 2 +O 2 ) started to decrease after an optimum at approximately 35 o C. However, there was a higher dependence of E on mean temperature of previous days than on mean temperature of current day for P. halepensis but not for Q. ilex. JCO 2 +O 2 showed a maximum relationship to mean temperature of previous 3 and 5 days for P. halepensis and Q. ilex respectively. We conclude that although the best correlation of emission rates were found for instantaneous foliar temperatures, the effect of accumulated previous temperature conditions should also be considered in models of monoterpene emission, especially for terpene storing species.
Keywords: acclimation; emission model; Pinus halepensis; previous climate effects; Quercus ilex